FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEMERINTAH DAERAH - Rustiyaningsih, Sri; Immanuela, Intan (Widya Warta, 2014)
The aims of this study were to investigate the effects of local government characteristics in Indonesia (size, local revenues, intergovernmental transfer, total expenditures, liabilities,population), and BPK audit findings on the performance of local governments. The sample was the local governments in Indonesia which presented the complete data. The secondarydata were collected using documentary method, and the hypotheses testing applied multiple regression analysis. The results showed that the size, intergovernmental transfer, totalexpenditures, liabilities, and BPK audit findings were not significant toward the performance of local governments. While, local revenues and population were significant toward theperformance of local governments.Key words: local government characteristics, BPK audit findings, local goverment performance